Neuromuscular adaptations following training and protein supplementation in a group of trained weightlifters - Taber, C.; Carroll, K.; DeWeese, B.; Sato, K.; Stuart, C.; Howell, M.; Hall, K.; Bazyler, C.; Stone, M. (Sports, 2018)
The purpose of this study was to examine the effects of a recovery supplement compared with a placebo on muscle morphology in trained weightlifters. Vastus lateralis and muscle fiber cross sectional area of type I and type II fibers were compared between groups using a series of 2 × 2 (group × time) repeated measure ANOVAs. Both groups on average improved cross-sectional area of the vastus lateralis, type I and type II muscle fibers from pre-to-post but individual response varied within both groups. Greater magnitude of changes in type I and type II muscle fibers were observed for the placebo group but not for vastus lateralis cross sectional area. Additionally, subjects were divided into large and small fiber groups based on combined fiber size at the start of the investigation. These findings indicate that the recovery supplement utilized provided no greater effect compared with a placebo in a 12-week block periodization protocol in trained weightlifters. The primary determinate of fiber size changes in the study was determined to be the initial fiber size of muscle fibers with larger practical changes observed in the small fiber group compared with the large fiber group in type I, II, and ultrasound cross-sectional area (CSA)